How 3D patient-specific instruments improve accuracy of pelvic bone tumour resection in a cadaveric study. Issue 10 (October 2017) - Sallent, A.; Vicente, M.; Reverté, M. M.; Lopez, A.; Rodríguez-Baeza, A.; Pérez-Domínguez, M.; Velez, R.
Abstract : Objectives: To assess the accuracy of patient-specific instruments (PSIs) versus standard manual technique and the precision of computer-assisted planning and PSI-guided osteotomies in pelvic tumour resection. Methods: CT scans were obtained from five female cadaveric pelvises. Five osteotomies were designed using Mimics software: sacroiliac, biplanar supra-acetabular, two parallel iliopubic and ischial. For cases of the left hemipelvis, PSIs were designed to guide standard oscillating saw osteotomies and later manufactured using 3D printing. Osteotomies were performed using the standard manual technique in cases of the right hemipelvis. Post-resection CT scans were quantitatively analysed. Student's t -test and Mann–Whitney U test were used. Results: Compared with the manual technique, PSI-guided osteotomies improved accuracy by a mean 9.6 mm (p < 0.008) in the sacroiliac osteotomies, 6.2 mm (p < 0.008) and 5.8 mm (p < 0.032) in the biplanar supra-acetabular, 3 mm (p < 0.016) in the ischial and 2.2 mm (p < 0.032) and 2.6 mm (p < 0.008) in the parallel iliopubic osteotomies, with a mean linear deviation of 4.9 mm (p < 0.001) for all osteotomies. Of the manual osteotomies, 53% (n = 16) had a linear deviation > 5 mm and 27% (n = 8) were > 10 mm. In the PSI cases, deviations were 10% (n = 3) and 0 % (n = 0), respectively. For angular deviation from pre-operative plans, we observed a mean improvement of 7.06° (p < 0.001) in pitch and 2.94° (p < 0.001) in roll, comparing PSI and the standard manual technique. Conclusion: In an experimental study, computer-assisted planning and PSIs improved accuracy in pelvic tumour resections, bringing osteotomy results closer to the parameters set in pre-operative planning, as compared with standard manual techniques. Cite this article : A. Sallent, M. Vicente, M. M. Reverté, A. Lopez, A. Rodríguez-Baeza, M. Pérez-Domínguez, R. Velez. How 3D patient-specific instruments improve accuracy of pelvic bone tumour resection in a cadaveric study. Bone Joint Res 2017;6:577–583. DOI: 10.1302/2046-3758.610.BJR-2017-0094.R1.